Produksi Ring Baut Diameter 16 x 4 mm Kepala Silinder, Bahan SS308, Kapasitas 12 Biji/Jam (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Bolt ring diameter 16 x 4 mm cylinder head, SS308 material on the cylinder head of a 250 cm³ motorcycle in 2013 is no longer produced by the factory, so its availability in the market is limited and difficult to obtain as a problem faced. The production objective is to obtain a bolt ring diameter 16 x 4 mm cylinder head, SS308 material on the cylinder head of a 250 cm³ motorcycle with a surface smoothness level of N7 in accordance with the standard component specifications. The production method includes: component design according to standards, selection of SS308 material with a diameter of 19.05 mm and a length of 1 m, turning to a diameter of 16 mm and a length of 200 mm, drilling with a diameter of 8 mm using a loose head to a depth of 50 mm, surface smoothing to a smoothness level of N7, cutting the material into 4 mm thick rings, and quality and dimension inspection. The production results are in the form of a bolt ring with an outer diameter of 16 mm, an inner diameter of 8 mm, a thickness of 4 mm which is installed on the cylinder head, SS308 material with a surface smoothness level of N7, a total production cost of IDR 9,500/piece, a production process duration of 5 minutes/piece which implies that the bolt ring is suitable for use on 250 cm³ motorcycles produced in 2013.